The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1186/s12245-021-00335-y
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of non-healthcare individuals towards cardiopulmonary resuscitation: a cross-sectional study in Riyadh City, Saudi Arabia

Abstract: Background Most sudden cardiac arrests occur at home, with low rates of bystander cardiopulmonary resuscitation being performed. We aimed to assess knowledge of cardiopulmonary resuscitation among individuals in Riyadh City, Saudi Arabia, who are not involved in health care. Methods A community-based cross-sectional study was conducted between January and February 2020 in 4 different areas in Riyadh City: North, South, East, and West. The participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…On the contrary, the other studies included all participants without exclusion of health care providers.Most participants with formal BLS training (38.8%) have received their training at universities and only 19.2% of participants with formal BLS training have received their training from television, the internet, and media.The participants showed some basic awareness of the signs of SCA, as the five most chosen signs were loss of consciousness (62.6%), chest pain (62.4%), loss of breathing (53.8%), difficulty breathing (52.2%), and pulselessness (44.1%). Those findings were similar to the findings of studies conducted in Riyadh and Turkey, in which they found the most chosen signs to be pulselessness (51.8% and 60.7% respectively), absence of breathing (48.1% and 49.3% respectively), and loss of consciousness (44.9% and 40.7%Alhussein et al, 2021;Özbilgin et al, 2015). Overall, participants in our study showed adequate knowledge in the assessment of the level of consciousness, breathing, and pulselessness, which was similar to a study conducted in Jeddah which showed that participants who had undergone CPR training can properly assess the consciousness level, breathing, and circulation(Qara et al, 2019).…”
supporting
confidence: 89%
See 2 more Smart Citations
“…On the contrary, the other studies included all participants without exclusion of health care providers.Most participants with formal BLS training (38.8%) have received their training at universities and only 19.2% of participants with formal BLS training have received their training from television, the internet, and media.The participants showed some basic awareness of the signs of SCA, as the five most chosen signs were loss of consciousness (62.6%), chest pain (62.4%), loss of breathing (53.8%), difficulty breathing (52.2%), and pulselessness (44.1%). Those findings were similar to the findings of studies conducted in Riyadh and Turkey, in which they found the most chosen signs to be pulselessness (51.8% and 60.7% respectively), absence of breathing (48.1% and 49.3% respectively), and loss of consciousness (44.9% and 40.7%Alhussein et al, 2021;Özbilgin et al, 2015). Overall, participants in our study showed adequate knowledge in the assessment of the level of consciousness, breathing, and pulselessness, which was similar to a study conducted in Jeddah which showed that participants who had undergone CPR training can properly assess the consciousness level, breathing, and circulation(Qara et al, 2019).…”
supporting
confidence: 89%
“…Furthermore, a study done in Riyadh found that 48.2% of participants expressed that they had underwent BLS training (Alhussein et al, 2021), in comparison to 25.6% in China, 40.3% in Turkey, and 56% in Australia (Chen et al, 2017; Aldhakhri and Can, 2020; Özbilgin et al, 2015;Cartledge et al, 2020). OHCA is also a significant problem in North America and in Europe (Gräsner et al, 2016).…”
Section: Medical Science L Analysis Articlementioning
confidence: 99%
See 1 more Smart Citation
“…concerns for woman 2% 291 resp. concerns for child 1% Cu 2009 [ 50 ] Caregivers of children presenting to the Emergency Department (≥18 years) 348 125 (unwilling to perform CPR on adult) 3% Hubble 2003 [ 61 ] High school students 683 NR 7% (MMV) 10% (AED) 6% (CC) Jelinek 2001 [ 64 ] General public (age not reported) 803 84 unwilling to perform MMV 56% Johnston 2003 [ 65 ] Adults (≥18 years) 4490 4490 4.50% Lester, Donnelly & Weston 1997 [ 84 ] First year high school pupils 233 233 11% Liaw et al 2020 [ 87 ] University employees (non-medical) 184 NR Fear and concern identified as significantly reduced by training in 34% Mathiesen et al 2017 [ 93 ] Witnesses of OHCA 10 10 NR (qualitative barrier identified) Sasson et al 2013 [ 114 ] Lay-people (min age not stated) 42 42 NR (1 of 10 qualitative barriers) Sasson et al 2015 [ 115 ] Lay-people (≥13) 64 64 NR (qualitative barrier identified) Concerns about risk of infection Alhussein 2021 [ 33 ] Adults (≥18) 856 Those whose source of k...…”
Section: Resultsmentioning
confidence: 99%
“…[10,11] Tenaga kesehatan maupun mahasiswa fakultas di bidang kesehatan telah mendapatkan pengetahuan dan ketrampilan semenjak duduk di bangku kuliah sehingga kemampuan mereka di atas rata-rata dalam pengenalan dan tatalaksana korban. [12,13] Bahkan di beberapa negara, murid sekolah lanjutan atas dan mahasiswa non bidang kesehatan juga telah diberikan pengetahuan dan ketrampilan dasar dalam pelaksanaan Bantuan Hidup Dasar. [14,15] Sedangkan para mahasiswa bidang kesehatan pasti memperoleh pengetahuan dan ketrampilan dasar dalam pelaksanaan Bantuan Hidup Dasar karena telah masuk dalam kurikulum.…”
Section: Abstrakunclassified